Nanocrystallization process in Finemet-type alloys followed by in situ 57Fe Mössbauer spectroscopy - Rodríguez V.A.P. (2004)
The authors are indebted to the group of Prof. Dr. A. Conde for sample supplies. This work was partially supported by the CONCYTEC of the Peruvian Government, by CNPq (PCI-program) of the Brazilian Government and by the Latin American Center of Physics. E. Baggio-Saitovitch thanks FAPERJ for the support as Cientista do Nosso Estado.